Pemahaman nilai pancasila dan prinsip continuous improvement terhadap implementasi cost reduction dalam mengurangi cost of quality PT. X - Masnur, Moh; Yulistia, Julia Ressi Irrenova; Pertiwi, Mutiara Widya; Devina, Angela Dea (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Indonesia has experienced significant growth in manufacturing investments, particularly in the non-oil and gas processing sector. One of the main challenges faced is the high cost of quality, arising from production defects and waste, which can reduce both profitability and competitiveness. This research aims to analyze the influence of understanding the values of Pancasila and the principles of Continuous Improvement (CI) on the implementation of cost reduction strategies to minimize quality costs resulting from production defects at PT. X. The study employs a quantitative approach with a survey method, using a Likert scale questionnaire administered to a sample of 76 employees out of a total population of 302 employees. The results indicate that both the understanding of Pancasila values (X1) and CI (X2) together significantly impact the implementation of cost reduction strategies, contributing 64.6% to the variation in the dependent variable. Individually, the CI variable has a dominant effect (β = 0.426; p < 0.05) compared to the Pancasila values (β = 0.127; p < 0.05). CI strategies, based on the PDCA cycle and Lean tools, have been shown to enhance operational efficiency, while Pancasila values foster an ethical and collaborative work culture.